'I'm picking a side': Thick solidarity, antiblackness and the grammar of the model minority. Issue 3 (4th May 2021) - Abad, Miguel N.
ABSTRACT: This article explores efforts by San Francisco based Asian American youth organizers to build meaningful cross-racial coalitions. Based upon two years of ethnographic field work with Fist Up, I offer an analysis of how youth organizers carried out the unsettling work of practicing what Roseann Liu and Savannah Shange have described as thick solidarity . Interrogating the model minority myth required that Asian American youth organizers develop sophisticated understandings its relationship to anti-Black political projects.